Question about The Learning Company Achieve! Math & Science Grades 1-3 (381933) for PC, Mac

Ad

6x- 3 = y; (0, -3)

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Posted on Sep 29, 2009

Ad

Hi there,

Save hours of searching online or wasting money on unnecessary repairs by talking to a 6YA Expert who can help you resolve this issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

Here's a link to this great service

Good luck!

Posted on Jan 02, 2017

Ad

The FX-901 calculator seems to be the equivalent of the FX 260 Solar sold in North America. It does fraction calculations, permutation, statistics but lack the Equation Solver.

You cannot use it to solve equations.

Casio Scientific calculators that can handle equation solving are the FX-115 and FX-991.

Simplify your first equation by dividing all its terms by 3, then use elimination to carry out the solution by hand.

You cannot use it to solve equations.

Casio Scientific calculators that can handle equation solving are the FX-115 and FX-991.

Simplify your first equation by dividing all its terms by 3, then use elimination to carry out the solution by hand.

Sep 02, 2012 | Office Equipment & Supplies

In equation mode, you have system of linear equations (3 unknown) you have polynomial (quadratic and cubic), and solver. Use the solver foe any type of equation (nonlinear, polynomial of order higher than 4, trigonometric, exponential, logs).

May 21, 2012 | Casio Scientific Calculator Fx-570 Fx570...

The x intercept is where your line will cross the x axis. Therefore, the value for y at this point is 0. Substitute 0 for y in this equation and solve for x.

6x + 3(0) = 27

x = 27/6

x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27

y = 27/3

y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

6x + 3(0) = 27

x = 27/6

x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27

y = 27/3

y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

May 18, 2012 | SoftMath Algebrator - Algebra Homework...

Calcualte the slope of the line as

a=(7-(-11))/(10-(-5))=18/15=6/5

Use the fact that the line passes through one of the two points, for example (10,7)

7=(6/5)*10+b=12+b

Obtain b as b=7-12=-5

The equation of the line in functional form is y=(6/5)x-5

Multiply everything by 5 to clear the fraction

5y=6x-25 or 0=6x-5y-25

Finally, the equation in general form (standard?) is**6x-5y-25=0**.

Check the calculation by verifying that the point (10,7) lies on the line.

6(10)-5(7)-25=60-35-25=60-60=0 CHECKed!

Check that the second point (-5,-11) lies on the line also (if you want to)

6*(-5)-5*(-11)-25=-30+55-25=0

That checks OK.

a=(7-(-11))/(10-(-5))=18/15=6/5

Use the fact that the line passes through one of the two points, for example (10,7)

7=(6/5)*10+b=12+b

Obtain b as b=7-12=-5

The equation of the line in functional form is y=(6/5)x-5

Multiply everything by 5 to clear the fraction

5y=6x-25 or 0=6x-5y-25

Finally, the equation in general form (standard?) is

Check the calculation by verifying that the point (10,7) lies on the line.

6(10)-5(7)-25=60-35-25=60-60=0 CHECKed!

Check that the second point (-5,-11) lies on the line also (if you want to)

6*(-5)-5*(-11)-25=-30+55-25=0

That checks OK.

Dec 04, 2011 | Super Tutor Pre Algebra (ESDPALG)

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

And your question is? If you just want to know how to solve this system, you only need to substitute one equation into the other and solve for the remaining unknown.

y=3x (equation 2), so plug it into equation 1

7x-2y=1

7x-2(3x)=1

7x-6x=1

x=1

from equation 2 then, you know y=3x=3

y=3x (equation 2), so plug it into equation 1

7x-2y=1

7x-2(3x)=1

7x-6x=1

x=1

from equation 2 then, you know y=3x=3

Oct 05, 2010 | Linear (HDMICAT5EXT) Repeater

The first step here is to draw a rough sketch of the two curves, and find the two points they meet. If you set x^3-6x^2+8x = x^3-4x, then you can rearrange this into the quadratic equation 6x^2-12x = 0. Solving this tells you x=0 or 2 : these are the two x values where the curves meet, and they give the bounds on your integral.

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

May 27, 2010 | Computers & Internet

This is easy. First these brackets ( ) have a three numbers followed by an x y and z, the brackets mean we should multiply the like amounts: but first lets group like amounts by adding them up 3x+16x+6x= 25x then 8y+9y+11y=28y, now z...13z+14z=27z now the otherside of the equation which is always after the equal sign is 326+453=779, so now it is more simplified by combining like amounts:so now we have 25x+28y++27z=779 so now we must balance both sides of thr equation, what we do to the left side of the equal sign, we must also do to the right side of the = sign, so we need to get x by itself, so we minus 25 and are left with just an x, then if we take 25 off of the other side of the = sign, we must take 779-25 so now x is on the left side by itself then the the right side is 754, so now the x is solved X=754, then you do the same for y and z.

Sep 22, 2009 | The Learning Company Achieve! Math &...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

2y - x = 3

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is**x = 1**, **y = 2**

or in ordered pair notation**(1, 2)**

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is

or in ordered pair notation

Jun 29, 2009 | Computers & Internet

183 people viewed this question

Usually answered in minutes!

×